Microwave link precipitation particle identification method based on multi-scale permutation entropy - TU JIE; CAO HUI; ZHANG YUSONG; ZHOU BAOHONG; YANG TAO; SHI PENGFEI; LIU SHUAI; YE WENJIE (2024)
The invention discloses a microwave link precipitation particle identification method based on multi-scale permutation entropy. The method comprises the following steps: acquiring multi-environment microwave link attenuation data and dividing the data according to the type of precipitation particles; performing multi-scale coarse graining on the attenuated signal data, and performing multi-scale permutation entropy calculation after result sequence reconstruction and probability calculation; calculating the average attenuation rate of each section of attenuation signal time sequence, and constructing an average attenuation rate-scale-permutation entropy three-dimensional data set; unifying the data size, dividing a training set and a test set, and training the constructed 2D-CNN network; and inputting microwave link data, and identifying precipitation particles by using the multi-scale permutation entropy and the trained network model. According to the method, the microwave signal time sequence can be subject